Analysis of the Three-Dimensional Dynamic Problems by Using a New Numerical Method - Rong, Yao; Sun, Yang; Zhu, LiQing; Xiao, Xiao (Advances in Civil Engineering, 2021)
The problems of the consolidation of saturated soil under dynamic loading are very complex. At present, numerical methods are widely used in the research. However, some traditional methods, such as the finite element method, involve more degrees of freedom, resulting in low computational efficiency. In this paper, the scaled boundary element method (SBFEM) is used to analyze the displacement and pore pressure response of saturated soil due to consolidation under dynamic load. The partial differential equations of linear problems are transformed into ordinary differential equations and solved along the radial direction. The coefficients in the equations are determined by approximate finite elements on the circumference. As a semianalytical method, the application of scaled boundary element method in soil-structure interaction is extended. Dealing with complex structures and structural nonlinearity, it can simulate two-phase saturated soil-structure dynamic interaction in infinite and finite domain, which has an important engineering practical value. Through the research, some conclusions are obtained. The dimension of the analytical problem can be reduced by one dimension if only the boundary surface is discretized. The SBFEM can automatically satisfy the radiation conditions at infinite distances. The 3D scaled boundary finite element equation for dynamic consolidation of saturated soils is not only accurate in finite element sense but also convenient in mathematical processing.